2015
DOI: 10.1007/s11069-015-1856-x
|View full text |Cite
|
Sign up to set email alerts
|

A multi-dimensional assessment of urban vulnerability to climate change in Sub-Saharan Africa

Abstract: In this paper, we develop and apply a multi-dimensional vulnerability assessment framework for understanding the impacts of climate change-induced hazards in Sub-Saharan African cities. The research was carried out within the European/African FP7 project CLimate change and Urban Vulnerability in Africa, which investigated climate change-induced risks, assessed vulnerability and proposed policy initiatives in five African cities. Dar es Salaam (Tanzania) was used as a main case with a particular focus on urban … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(25 citation statements)
references
References 36 publications
0
19
0
Order By: Relevance
“…There is no doubt that rapid ecological, social and economic transformation of urban centres is cause for unprecedented strains, not only to cities and local administrations, but also private households [64]. However, since climate change induced hazards, vulnerabilities and impacts are substantially increasing in urban environments, these changes will affect the livelihoods of the urban population, in particular the majority of poor and marginalised groups living in informal settlements.…”
Section: Day-to-day Struggles and Emerging Challenges In Sub-saharan mentioning
confidence: 99%
“…There is no doubt that rapid ecological, social and economic transformation of urban centres is cause for unprecedented strains, not only to cities and local administrations, but also private households [64]. However, since climate change induced hazards, vulnerabilities and impacts are substantially increasing in urban environments, these changes will affect the livelihoods of the urban population, in particular the majority of poor and marginalised groups living in informal settlements.…”
Section: Day-to-day Struggles and Emerging Challenges In Sub-saharan mentioning
confidence: 99%
“…There is also a growing effort to discourage people from building or farming in the flood plains and wetlands, however the effort is being resisted and politically contested [15]. To better adapt to urban flood, it is also suggested that climate change-related issues and strategies to encourage local participation should be incorporated into the planning process [16].…”
Section: Introductionmentioning
confidence: 99%
“…Our definition of vulnerability derives from the field of political economy, specifically using the approach by Adger and Kelly (, p. 254) who define vulnerability as “ the state of individuals, groups or communities in terms of their ability to cope with and adapt to any external stress placed on their livelihoods and well‐being. ” Vulnerability implies that some people are less or more susceptible than others, at different times and places (Crivello & Espinoza‐Revollo, ; Williams, ), to a specific hazard or range of hazards (Brooks, ) and vulnerability exists at different scales (Herslund et al, ). Importantly, people's vulnerability is not only a matter of individual resilience, but also exists in the idea of care as a manifestation of collective social responsibility (e.g., Crivello & Espinoza‐Revollo, ).…”
Section: The Climate Vulnerability Of the Urban Poormentioning
confidence: 99%